Genomic Study of a Clostridium difficile Multidrug Resistant Outbreak-Related Clone Reveals Novel Determinants of Resistance - Isidro, Joana; Menezes, Juliana; Serrano, Mónica; Borges, Vítor; Paixão, Pedro; Mimoso, Margarida; Martins, Filomena; Toscano, Cristina; Santos, Andrea; Henriques, Adriano O.; Oleastro, Mónica (Frontiers in Microbiology, 2018)
Background: Clostridium difficile infection (CDI) is prevalent in healthcare settings. The emergence of hypervirulent and antibiotic resistant strains has led to an increase in CDI incidence and frequent outbreaks. While the main virulence factors are the TcdA and TcdB toxins, antibiotic resistance is thought to play a key role in the infection by and dissemination of C. difficile. Methods: A CDI outbreak involving 12 patients was detected in a tertiary care hospital, in Lisbon, which extended from January to July, with a peak in February, in 2016. The C. difficile isolates, obtained from anaerobic culture of stool samples, were subjected to antimicrobial susceptibility testing with Etest® strips against 11 antibiotics, determination of toxin genes profile, PCR-ribotyping, multilocus variable-number tandem-repeat analysis (MLVA) and whole genome sequencing (WGS). Results: Of the 12 CDI cases detected, 11 isolates from different patients were characterized. All isolates were tcdA-/tcdB+ and belonged to ribotype 017, and showed high level resistance to clindamycin, erythromycin, gentamicin, imipenem, moxifloxacin, rifampicin and tetracycline. The isolates belonged to four genetically related MLVA types, with six isolates forming a clonal cluster. Three outbreak isolates, each from a different MLVA type, were selected for WGS. Bioinformatics analysis showed the presence of several resistance determinants, including the Thr82Ile substitution in gyrA, conferring moxifloxacin resistance, the substitutions His502Asn and Arg505Lys in rpoB for rifampicin resistance, the tetM gene, associated with tetracycline resistance, and two genes associated with aminoglycosides resistance, aadE and aac(6')-aph(2''). Furthermore, a not previously described 61.3 kb putative mobile element was identified, presenting a mosaic structure and containing the genes ermG, mefA/msrD and vat, associated with macrolide, lincosamide and streptogramins resistance. A substitution found in a class B penicillin-binding protein, Cys721Ser, is thought to contribute to imipenem resistance. Conclusions: We describe an epidemic, tcdA-/tcdB+, multidrug resistant clone of C. difficile from ribotype 017 associated with a hospital outbreak, providing further evidence that the lack of TcdA does not impair the infectious potential of these strains. We identified several determinants of antimicrobial resistance, including new ones located in mobile elements, highlighting the importance of horizontal gene transfer in the epidemiology of C. difficile.